2007
DOI: 10.1002/adsc.200600384
|View full text |Cite
|
Sign up to set email alerts
|

Dioxomolybdenum(VI)‐Catalyzed Reductive Cyclization of Nitroaromatics. Synthesis of Carbazoles and Indoles

Abstract: Reductive cyclization of nitrobiphenyls and nitrostyrenes to carbazoles and indoles, respectively, is carried out by triphenylphosphine under mild conditions catalyzed by a dichlorodioxomolybdenum(VI) complex. A one-pot procedure for the synthesis of regioselectively functionalized indoles has been developed from commercially available onitrobenzaldehydes and phosphoranes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
77
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 148 publications
(79 citation statements)
references
References 43 publications
1
77
0
1
Order By: Relevance
“…Interestingly, the present protocol, involving pinacol as reductant, allowed the selective reduction of 2-nitrobiphenyl to 2-aminobiphenyl (entries 4−5), whereas the corresponding reaction with the same dioxomolybdenum(VI) catalyst in the presence of triphenylphosphine as oxygen-acceptor exclusively afforded carbazole. [13] This result shows that under the pinacol-Mo VI catalytic system nitroso intermediates are probably not generated in significant amounts. The synthesis of anilines containing halides occurred in high yields regardless of their substitution pattern (Scheme 2 and Table 3, entries 7−16).…”
mentioning
confidence: 52%
See 1 more Smart Citation
“…Interestingly, the present protocol, involving pinacol as reductant, allowed the selective reduction of 2-nitrobiphenyl to 2-aminobiphenyl (entries 4−5), whereas the corresponding reaction with the same dioxomolybdenum(VI) catalyst in the presence of triphenylphosphine as oxygen-acceptor exclusively afforded carbazole. [13] This result shows that under the pinacol-Mo VI catalytic system nitroso intermediates are probably not generated in significant amounts. The synthesis of anilines containing halides occurred in high yields regardless of their substitution pattern (Scheme 2 and Table 3, entries 7−16).…”
mentioning
confidence: 52%
“…[10] In this field we have reported the first examples of the Mo-catalyzed deoxygenation of sulfoxides [11] and N-oxides, [12] as well as the reductive cyclization of nitroaromatics. [13] In those processes phosphorous(III)-based reagents were used as oxygen-acceptors. Later on, other authors have also reported similar dioxomolybdenum(VI)-catalyzed reactions using alternative reductants such as silanes, [14] boranes, [15] and hydrogen.…”
mentioning
confidence: 99%
“…[5c] as well as for the reductive cyclization of nitroaromatics, [9] using phosphorous(III) reagents as oxygen-acceptors. [10] Looking for greener reducing agents in this area, we have more recently found that diols, including glycerol, [11] are also useful reagents for the deoxygenation of some of these compounds.…”
mentioning
confidence: 99%
“…在各种环合反应中, 以硝基为环合基团的应用最为 广泛. Arnáiz 小组 [6] 以各种二取代的硝基联苯为原料, 如 Siamenol 等(Scheme 4). 以叠氮基为环合基团同样是合成咔唑的有效手段.…”
unclassified